The Acquisition of Requests in the Speech of Lithuanian Children - Kavaliauskaitė, Viktorija (Taikomoji kalbotyra, 2016)
This work focuses on early development of requests and investigates how and when these illocutionary acts are acquired by Lithuanian children. There are various ways to ask someone to do something. Expression of requests can vary according to the degree of directness depending on social context. These requests indicate communicative competence, development of pragmatics and politeness rules. The key aim of this study was to investigate types of requests and the sequence of those types first emerging in child speech.The study was based on the longitudinal data of two Lithuanian children, a girl Monika, aged 1;8–2;8, and a boy Elvijus, aged 1;6–2;7. The requests were also analyzed in child directed speech. According to the degree of directness and different types of requests, they were classified into direct (explicit performatives, imperatives, want / obligation statements, prohibitions), conventionally indirect (references to preconditions, hortatives) and non-conventionally indirect requests (hints, warnings).The results of the study demonstrate that direct requests were acquired first and they were the most common in children’s speech and in child directed speech. Firstly, the children formulate requests with nouns, the adverb more, verbs in 2SG imperative, the infinitive and hortative in 1PL present tense, they also use the modal verb want. Later, requests with nouns, infinitive and future tense disappear, the children’s requests start to resemble child directed requests. It was noticed that at the end of the second year the children started using formal and indirect requests. At the beginning of the third year, they acquire the basics how to formulate requests. Presumably, other Lithuanian children could demonstrate similar developmental patterns.
Keywords: psycholinguistics; children’s language acquisition; requests; expression of requests; children’s speech